Law, society, and history : themes in the legal sociology and legal history of Lawrence M. Friedman - Gordon, Robert W. (Robert Watson), 1941-; Horwitz, Morton J., 1938- (Cambridge : Cambridge University Press, 2011)
'This book assembles essays on legal sociology and legal history by an international group of distinguished scholars. All of them have been influenced by the eminent and prolific legal historian, legal sociologist, and scholar of comparative law, Lawrence M. Friedman. Not just a Festschrift of essays by colleagues and disciples, this volume presents a sustained examination and application of Friedman's ideas and methods. Some of the writers directly assess and comment on Friedman's vast body of work, while others examine his conclusions to see how well they have stood up over time. Various contributors apply concepts and insights derived from Friedman's work to the study of similar problems in different periods and societies. And others use Friedman's concepts and insights as a foil or contrast to their own approaches to studying law and society from theoretical perspectives very different from his. Together, the essays in this volume show the powerful ripple effects of Friedman's work on American and comparative legal sociology, American and comparative legal history, and the general sociology of law and legal change'--
Includes bibliographical references and index.
Keywords: Friedman, Lawrence Meir, -- 1930-; Sociological jurisprudence; Law -- History